The Structural and Optical Investigation of Grown GaN Film on Porous Silicon Substrate Prepared by PLD - Haneen Jabar; Makram Fakhri; Mohammed AbdulRazzaq; Subash C. B. Gopinath (Engineering and Technology Journal, 2023)
The optical properties of a grown gallium nitride (GaN) thin film on a porous silicon (P-Si) substrate was investigated. A Photo-electrochemical etching method was used to synthesize the Psi substrate, and a physical deposition method (pulsed laser deposition) of 1064 nm Q-switch Nd: YAG laser with a vacuum of 10−2 mbar was used to grow a thin layer of GaN on a prepared P-Si substrate. X-Ray diffraction displayed that GaN film has a high crystalline nature at the (002) plane. The photoluminescence of GaN film exhibited ultraviolet PL with a peak wavelength of 374 nm corresponding to GaN material and red PL with a peak wavelength of 730 nm corresponding to Psi substrate. The absorption coefficient of the P-Si substrate and grown GaN thin film was obtained from the absorption calculation of UV-Vis diffused spectroscopy at ambient temperature in the 230–1100 nm wavelength range. Extinction coefficients, optical energy gap, and refractive index of both the P-Si substrate and the grown GaN thin film have been determined, respectively. The direct optical energy gaps of both the P-Si substrate and grown GaN have also been determined using three methods: Plank’s relation with photoluminescence (PL) spectroscopy, Tauc'relation, and Kubulka-Munk argument with Uv-Vis diffused spectroscopy. It was observed that the optical energy gap of the P-Si substrate was 2.1 eV, while the grown GaN thin film had a multi-optical energy gap of 3.3 eV and 1.6 eV. A good agreement has been obtained between these mentioned methods.